2013
DOI: 10.1074/jbc.m113.486746
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Complex Recruits Epigenetic Regulators via Its Two Cyclin-dependent Kinase Subunits to Repress Transcription of Immune Response Genes

Abstract: Background: Two CDK subunits of the Mediator complex play pivotal roles in transcription by a mechanism that has not yet been elucidated. Results: The histone arginine methyltransferase PRMT5 is a Mediator CDK-interacting protein. Conclusion:Mediator-associated PRMT5 symmetrically dimethylates histone H4 arginine 3, and this might cause transcriptional repression. Significance: This work enables further exploration of Mediator functions in transcriptional repression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 60 publications
2
40
1
Order By: Relevance
“…CTGF is a secreted signaling molecule, usually crosstalking with the TGF-β signaling pathway, and is reported to regulate the proliferation of pancreatic cancer cells27. Nedd9 is an intracellular scaffolding protein that serves as a downstream gene of the Wnt/β-catenin signaling pathway28, CDK19, a homologous protein of CDK8 (both proteins are components of the mediator complex), uploads the RNA polymerase II transcription machinery and gene-specific transcription factors29. It has been reported that CTGF30, Nedd931, and CDK1931 genes are targets of miR-18a in human cancer cells, and IGF132 is a miR-18a target in deer antler.…”
Section: Resultsmentioning
confidence: 99%
“…CTGF is a secreted signaling molecule, usually crosstalking with the TGF-β signaling pathway, and is reported to regulate the proliferation of pancreatic cancer cells27. Nedd9 is an intracellular scaffolding protein that serves as a downstream gene of the Wnt/β-catenin signaling pathway28, CDK19, a homologous protein of CDK8 (both proteins are components of the mediator complex), uploads the RNA polymerase II transcription machinery and gene-specific transcription factors29. It has been reported that CTGF30, Nedd931, and CDK1931 genes are targets of miR-18a in human cancer cells, and IGF132 is a miR-18a target in deer antler.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was extracted as described above, and biotinylated transcripts were purified with streptavidin Dynabeads (Invitrogen). cDNA was produced directly from the beads by use of random hexamer primers and subjected to qPCR with the EGR1-specific primers defined above (40). The positions of the 5= ends of these primers are ϩ588 and ϩ1308 with respect to the start of transcription.…”
Section: Methodsmentioning
confidence: 99%
“…CDK8 also regulates itself via autophosphorylation and further regulates transcription by phosphorylating a number of transcriptional regulators, such as cyclin H, MED13, histone H3, and the transcription factors E2F1, STAT1, and SREBP-1 (20,23,26,27,(31)(32)(33)(34)(35)(36)(37)(38)(39). These phosphorylation events change the epigenetic structure of chromatin and enhance or repress the rate of RNA Pol II transcription initiation and elongation (23,36,(40)(41)(42)(43)(44). The result of these transcriptional changes is the activation or inhibition of gene expression in response to a variety of stimuli, including hormones, cytokines, hypoxia, or serum (growth factors) (23,26,31,38,(41)(42)(43)(44)(45)(46).…”
mentioning
confidence: 99%
“…Furthermore, MED12 mutations found in patients with X-linked intellectual disability attenuated the ability of Mediator to recruit G9a and induced abnormal neuronal gene expression (Ding et al, 2008). In another report, the two kinase subunits of Mediator, CDK8 and CDK19, were shown to interact with the histone arginine methyltransferase PRMT5 and WD-repeat protein 77 (WDR77; also known as MEP50), respectively, both of which are important for further recruitment of the DNA methyltransferase DNMT3A and subsequent repression of C/EBPβ-regulated genes (Tsutsui et al, 2013). Thus, individual Mediator components appear to exhibit specificity for distinct epigenetic events, such as the recruitment of specific histone or DNA modifiers which, in turn, influence specific epigenetic modifications.…”
Section: Mediator and Epigenetic Regulatorsmentioning
confidence: 99%